Advancement in recombinant protein production using a marine oxygen carrier to enhance oxygen transfer in a CHO-S cell line. (June 2015) - Le Pape, Fiona; Bossard, Morgane; Dutheil, Delphine; Rousselot, Morgane; Polard, Valérie; Férec, Claude; Leize, Elisabeth; Delépine, Pascal; Zal, Franck
Abstract Recombinant proteins, particularly proteins used as therapeutics, are widely expressed for bioprocessing manufacturing processes. Mammalian cell lines represent the major host cells for bioproduction, according to their capacities of post-translational modifications and folding of secreted proteins. Many parameters can affect cell productivity, especially the rate of oxygen transfer. Dissolved oxygen, in high or low proportions, is a crucial parameter which can affect cell viability and thus productivity. HEMARINA has developed a new technology, commercially proposed as HEMOXCell®, to improve cell culture at a large production scale. HEMOXCell® is a marine oxygen carrier having properties of high oxygen sensitivity, to be used as an oxygen additive during cell culture manufacturing. In this study, we investigated the effects of HEMOXCell® on the culture of the commonly used CHO-S cell line. Two main objectives were pursued: 1) cell growth rate and viability during a batch mode process, and 2) the determination of the effect of this oxygen carrier on recombinant protein production from a CHO-transfected cell line. Our results show an increase of CHO-S cellular growth at a rate of more than four-fold in culture with HEMOXCell®. Moreover, an extension of the growth exponential phase and high cell viability were observed. All of these benefits seem to contribute to the improvement of recombinant protein production. This work underlines several applications using this marine-type oxygen carrier for large biomanufacturing. It is a promising cell culture additive according to the increasing demand for therapeutic products such as monoclonal antibodies.